Computational Review and Assessment of The Urban Heat Island Effect and Its Impact on Building Space Conditioning - Banerjee, Debanjali (Enquiry The ARCC Journal for Architectural Research, 2023)
This paper reviews and reports the recent progress and knowledge on the specific impact of the urban heat island (UHI) effect on building space conditioning for vulnerable housing where lack of air conditioning and fuel poverty causes indoor overheating, thus increasing vulnerability. Previous studies demonstrated that the increase of the ambient temperature due to UHI and heat waves impacts adversely cooling energy consumption of buildings and raises the peak electricity demand during summer and heat waves. Given the aging and dilapidated housing conditions in low-income communities, mostly of color and minorities, the economic burden of the cooling energy penalty induced by urban overheating is higher. However, literature on overheating is primarily driven by the physical characteristics of the building such as insulation, albedo, and envelope properties, and the Heat Vulnerability Index (HVI) by demographic data such as age, income, education largely remains isolated thus failing to capture the overall understanding of heat vulnerability and the role architects/urban designers can play in mitigation. Through a computational query review of the last fifteen years of publication, we are inquiring, about how UHI impacts building energy consumption in low-income and poor-quality housing and what role city and housing characteristics play in indoor overheating. Our study suggests, that in the US, due to segregated historic planning policies, low-income houses are often located in low tree canopy areas with varying urban typologies, and higher impervious material which substantially increases the air temperature thus determining energy consumption and anthropogenic heat release which contribute to present-day inequitable exposure to intra-urban heat. Both housing characteristics and the location of housing play a crucial role as similar housing will experience different exposure to intra-urban heat if not located in a heat canyon. Through this literature review, it became evident that there is a gap in the research that fails to connect building characteristics and overheating with heat vulnerability. Research involving UHI and heat vulnerability has continued to advance through energy analysis and mitigation studies, but future studies need to redefine the HVI index, especially by incorporating city and housing characteristics, which can help architects/urban designers make informed design decisions.